Efficacy and safety of empagliflozin in Japanese patients with type 2 diabetes mellitus: A sub-analysis by body mass index and age of pooled data from three clinical trials. (September 2017) - Shiba, Teruo; Ishii, So; Okamura, Tomoo; Mitsuyoshi, Rika; Pfarr, Egon; Koiwai, Kazuki
Highlights: Analysis was conducted using a pooled data from Japanese patients with T2DM. Empagliflozin improved HbA1c, FPG and weight, regardless of age and obesity. Empagliflozin was well tolerated for treating a wide range of Japanese patients. Abstract: Aims: To investigate the efficacy and safety of empagliflozin in subgroups based on body mass index (BMI) and age, using a pooled data set from Japanese patients with type 2 diabetes mellitus (T2DM). Methods: Pooled data from 1403 patients treated with empagliflozin at 10 mg/day or 25 mg/day in three clinical studies (≥52 week treatment) were stratified by baseline BMI (<22, 22 to <25 and ≥25 kg/m 2 ) and baseline age (<50, 50 to <65 and ≥65 years). Results: Empagliflozin at 10 mg/day and 25 mg/day reduced mean glycated hemoglobin (HbA1c) (−0.77 to −0.87% and −0.76 to −0.97%, respectively), mean fasting plasma glucose (FPG) (−20.79 to −27.06 mg/dL and −26.08 to −29.60 mg/dL) and mean body weight (−3.4 to −4.7% and −3.7 to −4.7%) in all subgroups of baseline BMI and age, regardless of age and degree of obesity. Adverse events were observed in approximately 70–80% patients in BMI and age subgroups of both empagliflozin groups. No hypoglycemia requiring assistance was observed. Neither UTI nor genital infection rates differed markedly among the BMI and age subgroups. Volume depletion was increased in patients ≥65 years of age as compared to younger patients. Conclusions: Empagliflozin was well tolerated and improved HbA1c, FPG and body weight in all BMI and age subgroups of Japanese patients with T2DM, regardless of age and degree of obesity. Empagliflozin is considered to be effective and well tolerated for treating a wide range of Japanese patients with T2DM. Trial registration: Study 1 (NCT01193218 ), Study 2 (NCT01289990 ) and Study 3 (NCT01368081 ).